Technology roadmap for development of SiC sensors at plasma processes laboratory - Fraga,Mariana Amorim (2010)
Abstract: Recognizing the need to consolidate the research and development (R&D) activities in microelectronics fields in a strategic manner, the Plasma Processes Laboratory of the Technological Institute of Aeronautics (LPP-ITA) has established a technology roadmap to serve as a guide for activities related to development of sensors based on silicon carbide (SiC) thin films. These sensors have also potential interest to the aerospace field due to their ability to operate in harsh environment such as high temperatures and intense radiation. In the present paper, this roadmap is described and presented in four main sections: i) introduction, ii) what we have already done in the past, iii) what we are doing in this moment, and iv) our targets up to 2015. The critical technological issues were evaluated for different categories: SiC deposition techniques, SiC processing techniques for sensors fabrication and sensors characterization. This roadmap also presents a shared vision of how R&D activities in microelectronics should develop over the next five years in our laboratory.